Reversible cerebral vasoconstriction syndrome with basilar artery stenosis: A case report. Issue 38 (24th September 2021) - Joh, Sang Woo; Kim, Sang Yeon; Shin, Byoung-Soo; Kang, Hyun Goo
Abstract: Introduction: Acute severe headaches in young patients may be associated with fatal neurological complications that necessitate imaging examinations. Among acute severe headaches, a thunderclap headache may indicate the rupture of a cerebral aneurysm or the onset of reversible cerebral vasoconstriction syndrome for which emergent evaluation is required. Patient concerns: We report the case of a 36-year-old man who presented to our hospital with an acute severe headache after excessive exercise the previous day. He was prescribed a pain reliever and discharged under the suspicion of vestibular migraine but returned to the emergency room after 4 hours due to right hemiparesis, right facial palsy, severe dysarthria, and a mild drowsy mental status. Diagnosis: After cerebral angiography, we diagnosed basilar artery stenosis with acute infarction in the posterior circulation due to reversible cerebral vasoconstriction syndrome. Interventions: Brain computed tomography angiography revealed complete occlusion of the vertebrobasilar artery. Transfemoral cerebral angiography showed spontaneous improvement in the occlusion before thrombectomy. Outcomes: Ten months later, high-resolution vessel wall magnetic resonance angiography showed persisting severe stenosis of the basilar artery. Conclusions: A headache in young patients with risk factors of atherosclerosis, such as smoking history, uncontrolled hypertension, and dyslipidemia may be caused by reversible cerebral vasoconstriction syndrome or ischemic stroke, which has fatal neurological complications. Therefore, reversible cerebral vasoconstriction syndrome or ischemic stroke should be suspected and appropriately evaluated in such patients, even if the headache is not the thunderclap type.